Biogenically Synthesized Polysaccharides-Capped Silver Nanoparticles: Immunomodulatory and Antibacterial Potentialities Against Resistant Pseudomonas aeruginosa - El-Deeb, Nehal M.; Abo-Eleneen, Mai A.; Al-Madboly, Lamiaa A.; Sharaf, Mona M.; Othman, Sarah S.; Ibrahim, Omar M.; Mubarak, Mohammad S. (Frontiers in Bioengineering and Biotechnology, 2020)
Bacterial infections are the key cause of death in patients suffering from burns and diabetic wounds while the use of traditional antibiotics has been growing steadily. Thus, in the present study, we were trying to introduce a paradigm shift strategy to improve chronic wound healing of bacterial infection. To that end, we have biologically synthesized silver nanoparticles (AgNPs) using Arthrospira sp polysaccharides, and evaluated their antibacterial efficacy with their safety pattern. Scanning electron micrographs showed spherical AgNPs coated with algal polysaccharides with an approximate size of 9.7 nm. Treatment of Pseudomonas aeruginosa with the AgNPs (0.5–1 µg/mL) resulted in a significant disruption in P. aeruginosa outer membrane, reduction in biofilm formation, and a significant decrease of production of alginate and pyocyanin along with a concentration-dependent reduction in β-lactamase activity. In addition, at the in vivo level, AgNPs displayed substantial activity to control P. aeruginosa infections in rat skin wounds with significant reduction in in COX-2 enzyme in both rat skin homogenate and serum samples. Furthermore, AgNPs facilitated wound curative in the P. aeruginosa infected model by reducing the hemorrhagic areas number and the infiltrated inflammatory cells. Taken all together, these biogenic nanoparticles showed unique properties in controlling bacterial wound infections and improving the healing process of damaged tissues via its direct and indirect effects.